2023
DOI: 10.1007/s00198-023-06837-0
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization analysis of osteoporosis medications in seven European electronic health databases

Abstract: Summary We studied the characteristics of patients prescribed osteoporosis medication and patterns of use in European databases. Patients were mostly female, older, had hypertension. There was suboptimal persistence particularly for oral medications. Our findings would be useful to healthcare providers to focus their resources on improving persistence to specific osteoporosis treatments. Purpose To characterise the patients prescribed osteoporosis therapy and describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“… 24 Sixty-six percent of respondents reported that adjuvant intravenous bisphosphonate use had been impacted by the pandemic in terms of delayed treatment, missed appointments and reduced clinical capacity, requiring a switch from intravenous to oral administration, while nearly a quarter of respondents reported decreased use of oral bisphosphonates. This is in line with our results, which show that bisphosphonate prescriptions were indeed reduced across the pandemic for breast cancer patients on AIs (though it should be noted that this pattern is seen in other populations, not limited to cancer patients 25 ).…”
Section: Discussionsupporting
confidence: 92%
“… 24 Sixty-six percent of respondents reported that adjuvant intravenous bisphosphonate use had been impacted by the pandemic in terms of delayed treatment, missed appointments and reduced clinical capacity, requiring a switch from intravenous to oral administration, while nearly a quarter of respondents reported decreased use of oral bisphosphonates. This is in line with our results, which show that bisphosphonate prescriptions were indeed reduced across the pandemic for breast cancer patients on AIs (though it should be noted that this pattern is seen in other populations, not limited to cancer patients 25 ).…”
Section: Discussionsupporting
confidence: 92%
“…Sixty-six percent of respondents reported that adjuvant intravenous bisphosphonate use had been impacted by the pandemic, in terms of delayed treatment, missed appointments, and reduced clinical capacity, requiring a switch from intravenous to oral administra on; whilst nearly a quarter of respondents reported decreased use of oral bisphosphonates. This is in line with our results which show that prescrip ons of bisphosphonates were indeed reduced across the pandemic for breast cancer pa ents on AIs (though it should be noted that this pa ern is seen in other popula ons, not limited to cancer pa ents [24]).…”
Section: Discussionsupporting
confidence: 92%